A facile one-step strategy for development of a double network fibrous scaffold for nerve tissue engineering. (28th April 2017) - Golafshan, Nasim; Gharibi, Hamidreza; Kharaziha, Mahshid; Fathi, Mohammadhossein
Abstract: The aim of this study was to develop a novel double network scaffold composed of polycaprolactone fumarate (PCLF) and eggshell membrane (ESM) (ESM:PCLF) by using the vacuum infiltration method. Compared to ESM, the mechanical properties of double network scaffold were significantly improved, depending on the solvents applied for double network scaffold formation; acetic acid and dichloromethane. Noticeably, the toughness and strength of double network scaffold prepared using acetic acid were significantly improved compared to ESM (26.6 and 25 times, respectively) attributed to the existence of hydrophilic functional groups in acetic acid which made ESM flexible to absorb further PCLF solution. To assess the effect of double network formation on the biological behavior of ESM, the attachment, proliferation and spreading of PC12 cells cultured on the ESM:PCLF scaffolds were evaluated. Results revealed that the number of cells attached on double network ESM:PCLF scaffold were nearly similar to ESM and significantly higher than that of on the tissue culture plate (2.6 times) and PCLF film (1.7 times). It is envisioned that the offered ESM:PCLF double network scaffold might have great potential to develop the constructs for nerve regeneration.